The relevance of the transition to a circular economy for Ukraine - S. Voitko; A. Vyshnevska (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
The article deals with the problem of solid waste accumulation in the world and in Ukraine. The volumes of municipal solid waste and its distribution in different regions of the world are analyzed. The importance of efficient waste collection as a key aspect of waste management is emphasized, as well as the need for immediate measures to prevent further deterioration of the environmental situation. The article presents an analysis of the pre-war situation with waste management in Ukraine in terms of such indicators as the dynamics of waste generation and the share of its recycling, the number of operating business entities of various sizes in the field of waste processing. In addition, the article highlights the impact of military events on the environmental situation in the country and emphasizes the need for changes to build a sustainable economy, which may be possible through post-war recovery. In the context of finding solutions to reduce the negative impact of waste on the environment, the authors consider the concept of circular economy, which involves production aimed at reusing resources and reducing the volume of waste generation in order to ensure sustainable development. The basic principles of the circular economy and the hierarchy of waste management that has been formed in the EU are presented. In addition, the article presents the main program documents in Ukraine aimed at developing the circular economy, such as national strategies, plans and concepts. The article also examines the obstacles to the successful implementation of circular economy principles in Ukraine, such as imperfect regulatory framework, insufficient funding for environmental protection and waste management, and the lack of an integrated approach at various levels of the economy. Based on the analysis, the authors conclude that it is necessary to intensify efforts to implement the principles of the circular economy at Ukrainian enterprises. The authors emphasize the need to create incentives for innovation and investment in modern technologies to reduce the harmful effects of waste on the environment.